Prevalence of falls among older people physically independent: An analysis of occurrence in 12 months: Prevalence of falls in the elderly - A. Gagliardi, Paula; A. Alves, Davi; B. O. Vasconcelos, Fernanda; B. Mazieri, Nathan; G. Ruivo, Leonardo; S. Revoredo, Juliana; T. Yabushita, Fernando; R. Oliveira, Márcio (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: Physically independent older adults are considered active in daily life activities. However, as age progresses, physiological changes increase the risk of falls. Thus, any obstacle requiring attention, balance, and/or reaction may result in a fall. Objective: To present the prevalence of falls among older adults 12 months after the assessment of overall strength and functional reach during the pandemic. Methods: This is a longitudinal and observational study involving 69 older adults of both sexes (age: 69 ± 7 years; body mass index: 27 ± 4 kg/m²). Participants answered a structured interview with questions about the occurrence of falls after 12 months. Additionally, data from handgrip strength and functional reach assessments contributed to understanding participants’ functionality. Results: The majority of the studied population consisted of women (88%). Over the 12-month period, 80% of participants did not experience falls. Among those who fell, the main consequences were fractures (8%) and ankle sprains (8%), occurring predominantly in women. The most frequently reported fall locations were sidewalks (36%), homes (29%), streets (21%), and yards (14%). Tripping was the primary cause of falls, reported by 57% of participants. Finally, reduced handgrip strength was observed in 9% of men and 16% of women, while reduced functional reach was identified in 1% of men and 24% of women. Conclusion: The findings of this study indicate that the incidence of falls among older adults evaluated after 12 months was 20%, with no major consequences such as hospitalization or disabling injuries. Additionally, falls occurred predominantly in women and in public environments, especially on sidewalks.